The optimizing Ar-Rahnu service for the growth of achievement at Bank Rakyat Senawang Branch / Nur Ain Mohd Sazali - Mohd Sazali, Nur Ain (2011)
Ar-Rahnu scheme at Bank Rakyat Senawang branch reach out the outstanding achievement by year to year. Basically, Bank Rakyat Senawang branch aims is to provide efficiency and set strategy to meet the total needs of customers and adaptable to changing perception by customer to using Ar-Rahnu scheme. This research is designed because the product called Ar-Rahnu able to be marketed and can be catalyst for the growth of achievement in Bank Rakyat Senawang. The demand of the product that highly demanded in every month and shows that customers believed on the system of Ar-Rahnu service and knows the advantage of the product. This research uses the Statistical for Social Science (SPSS) VERSION 17.0 to analyze the data from questionnaires. The secondary data, this research use the Bank Rakyat’s annual report to find the information about the Ar-Rahnu achievement indicator from 2007 to 2010.The issues that could be raised here are: first, to determine the level of customers’ awareness on system of Islamic pawnbroking that reflects on growth of the achievement at Bank Kerjasama Rakyat Senawang branch. And second to determine the changing perception towards Islamic pawnbroking that relate to the growth of the achievement at Bank Kerjasama Rakyat Senawang branch.